Mediating Role of Crisis Management between Knowledge Management and Employee Commitment - Abdalla Hassan sahako Aldhuhoor, Hassan; Din, Badariah binti Haji; Saoula, Oussama (South Asian Journal of Social Sciences and Humanities, 2023)
The purpose of the study is to examine the mediating role of crisis management between knowledge management and employee commitment. Committed employees are needed to keep the workforce motivated and knowledge is required to keep them committed, however, crisis issues develop loyalty among the employees, and this can only be achieved if the employees effectively manage knowledge. For the purpose of achieving the objectives of the study, primary study has been conducted. A sample of 384 employees was used to run structural equation modeling. The findings revealed that knowledge management has a significant impact over employee commitment, likewise, crisis management significantly mediates the positive relationship between knowledge management and employee commitment. The study used the underpinning support of knowledge-based view, and it is an attempt to enrich the theory by adding crisis management in the theory as a mediator.